2002
DOI: 10.1046/j.1365-3121.2002.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Flood and earthquake disturbance of 210Pb geochronology (Lake Anterne, NW Alps)

Abstract: Dating recent lake sediment records yielding disturbed 210Pb profiles has been a problem of wide interest in palaeoclimatic and palaeoseismic studies over the last few centuries. When applied to an alpine lake sedimentary record, a high‐resolution sedimentological study reveals that the 210Pb profile is disturbed by the occurrence of single‐event deposits triggered by two different mechanisms: flood events deposits and gravity reworking. Removing disturbed layers from the 210Pb profile yields a logarithmic dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
148
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(160 citation statements)
references
References 16 publications
9
148
0
3
Order By: Relevance
“…formation of concentrated density flows of suspended sediments during a subaquatic mass movement (e.g. Mulder and Cochonnat, 1996;Arnaud et al, 2002;Wilhelm et al, 2016b). The HB characteristics are very similar to deposits previously described by many studies (e.g.…”
Section: Trigger Of Msb Hb Gb-iii and The Deformed Layersupporting
confidence: 82%
See 2 more Smart Citations
“…formation of concentrated density flows of suspended sediments during a subaquatic mass movement (e.g. Mulder and Cochonnat, 1996;Arnaud et al, 2002;Wilhelm et al, 2016b). The HB characteristics are very similar to deposits previously described by many studies (e.g.…”
Section: Trigger Of Msb Hb Gb-iii and The Deformed Layersupporting
confidence: 82%
“…5). We excluded 210 Pbex values associated with these instantaneous deposits to construct a synthetic sediment record (Arnaud et al, 2002). The CFCS model (Goldberg, 1963) was applied to the synthetic 210 Pbex profile and indicates that the sequence is characterized by two periods of different sedimentation rates.…”
Section: Chronologymentioning
confidence: 99%
See 1 more Smart Citation
“…Visual identification was based on the sedimentological features of these deposits. These features are characterized by the succession of three phases that become finer upward 36,41 from bottom to top as follows: coarse and well-sorted sediments; a mixture of silts and fine sands; and a layer of fine silts and clays. The thickness of these erosive deposits varies from 0.5 to 27 cm.…”
Section: Methodsmentioning
confidence: 99%
“…In turn, information on sedimentation processes may allow for inferences of key environment changes in the past, e.g. floods, earthquakes, fire, or human reclamation events (Arnaud et al, 2002;Moreno et al, 2008) and although sediment disturbances can be disadvantageous, numerous palaeolimnological studies have revealed that a reasonable chronology can be achieved, especially where multicore comparisons allow sediment disturbances to be distinguished (Tibby 2001;Donovan and Grimm, 2007;Morellón et al, 2011).…”
mentioning
confidence: 99%